2011
DOI: 10.1099/mic.0.049544-0
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas hydrophila motY is essential for polar flagellum function, and requires coordinate expression of motX and Pom proteins

Abstract: By the analysis of the Aeromonas hydrophila ATCC7966T genome we identified A. hydrophila AH-3 MotY. A. hydrophila MotY, like MotX, is essential for the polar flagellum function energized by an electrochemical potential of Na+ as coupling ion, but is not involved in lateral flagella function energized by the proton motive force. Thus, the A. hydrophila polar flagellum stator is a complex integrated by two essential proteins, MotX and MotY, which interact with one of two redundant pairs of proteins, PomAB and Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
1
12
0
7
Order By: Relevance
“…This suggests that other strains of A. piscicola are also able to adhere to and invade fish cells. Two essential proteins (motY and motX) for the motility of the polar flagellum have also been recognized using mutant strains of AH3 (Molero et al 2011). Yeh & Klesius (2011) amplified and purified 19 A. hydrophila flagellar proteins and found that one of them, the FlgK protein (which is a flagellar hook-filament junction protein involved in bacterial motility, colonization and invasion) showed a strong reaction against the sera of infected channel catfish.…”
Section: Structural Components (Adhesins)mentioning
confidence: 99%
“…This suggests that other strains of A. piscicola are also able to adhere to and invade fish cells. Two essential proteins (motY and motX) for the motility of the polar flagellum have also been recognized using mutant strains of AH3 (Molero et al 2011). Yeh & Klesius (2011) amplified and purified 19 A. hydrophila flagellar proteins and found that one of them, the FlgK protein (which is a flagellar hook-filament junction protein involved in bacterial motility, colonization and invasion) showed a strong reaction against the sera of infected channel catfish.…”
Section: Structural Components (Adhesins)mentioning
confidence: 99%
“…Region 5 of Vibrio and Pseudomonas includes a gene that encodes the motor protein MotY, however in Aeromonas it contains the master regulatory genes ( flrABC ). Recently, the Aeromonas MotY has been found in a different region with different behavior than the Vibrio MotY [179]. …”
Section: Motility and Flagellamentioning
confidence: 99%
“…Proper stator recruitment and activity has been demonstrated to depend on several components within the flagellar motor. One of these components is the T-ring which is formed by the MotX and Y proteins in many Na 1 -dependent motors, such as those of Vibrio, Shewanella or Aeromonas (Terashima et al, 2006;Koerdt et al, 2009;Molero et al, 2011). MotX and MotY are also needed for MotAB function in S. oneidensis .…”
Section: Motxy Are Required For Motab* Activitymentioning
confidence: 99%